A Comparison of the Mechanical Properties of Two External Fixator Designs for Transarticular Stabilization of the Canine Hock - Wells, K. L.; Pardo, A. D.; Parrott, M. B.; Wassermann, J. F. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Biomechanical testing was performed on 20 canine tibiotarsal joints. The conventional transarticular external skeletal fixator (ESF) was applied to one rear limb while the alternative design using acrylic was applied to the contralateral rear limb. The mode of failure for all models was fracture of the phalanges at the point of fixation in the distal grip device.The mean stiffness for the acrylic design was 58.5 N/mm and for the conventional ESF 44.8 N/mm. The mean maximum load to failure for the acrylic design was 490.7 N, compared to 405.1 N for the conventional ESF. The angle of deformation at maximum for the acrylic apparatus was 0.45 degrees compared to 2.36 degrees for the standard ESF. The mean energy absorbed to maximum load was 1.92 N-m for the acrylic design and for the conventional ESF 2.69 N-m. This study indicated that the acrylic design was superior in maintaining immobilization across the tibiotarsal joint, indicated by the angle of deformation (p = 0.002) and was structurally comparable in stiffness (p = 0.295), maximum strength (p = 0.438), and total energy absorbed to failure (p = 0.276).The properties of an acrylic and a stainless steel external transarticular skeletal fixator were biomechanically evaluated. Biomechanical parameters evaluated included: maximum load to failure, stiffness, angle of deformation across the tibiotarsal joint, and energy absorbed to failure. The angle of deformation was less (p = 0.002) for the acrylic device. Based on this study, we conclude that the new acrylic design is structurally comparable to the conventional transarticular ESF and warrants clinical trials.
Keywords: External fixation; methylmethacrylate; transarticular